Peran Layanan Digital bagi UMKM dalam Mendorong Peningkatan Inklusi Keuangan - Widyatmoko Widyatmoko; Tri Esti Rahayuningtyas; Ery Mintorini (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to be able to find out and analyze the relationship between the financial performance of micro, small and medium enterprises or MSMESs and knowledge of financial inclusion towards the implementation of digitization in order to assist and facilitate financial inclusion activities towards public knowledge. This study uses a descriptive quantitative research method. The results of the research are data processing using SPSS 26 statistics and the results show that financial inclusion can trigger an increase in public knowledge or micro, small and medium enterprises, and financial inclusion can improve financial performance with knowledge of existing products in banking institutions with digital technology facilities. From the results of the study it can be concluded that MSMEs business actors have a partial effect on the use of digital technology services. Likewise, the knowledge variable about financial inclusion has a partial effect on the use of digital technology services. Keywords: Digital, Financial Inclusion, Micro, Small and Medium Enterprises